Podoplanin and ABCG2 expression in oral erythroplakia revisited: Potential evidence for cancer stem cells driving the process of field cancerization. (February 2020) - Yang, Xi; Shi, Linjun; Zhou, Zengtong; Liu, Wei
Abstract: A model of field cancerization orchestrated by the cancer stem cells (CSC) was proposed. Podoplanin and ABCG2 are promising marker of CSCs for head and neck cancer. We revisited the correlation of the two markers with the follow-up data of the patients with oral erythroplakia (OE). Strikingly, we observed that the expression of podoplanin and ABCG2 within a single pre-neoplastic OE lesion significantly correlate with subsequently developing multiple and multifocal carcinomas, thus to some extent demonstrating the concept of field cancerization. Collectively, a point to highlight was that a preliminary evidence that provided by this revisited study supported the perspective on cancer stem cells driving the process of field cancerization.